Assessment of Factors Affecting the Difficulty of Caudal Epidural Injections in Adults Using Ultrasound - Young Hoon Kim; Hue Jung Park; Sungkun Cho; Dong Eon Moon (Pain Research and Management)
BACKGROUND: In unaided caudal epidural block (CEB), incorrect needle insertion has been reported to occur in 15% to 38% of attempts.